A Revolutionary Approach Using Artificial Intelligence and Quantum Cryptography – A Review - Najma Imtiaz Ali; Imtiaz Ali Brohi; Jamali, Mujeeb-ur-Rehman; Mazhar Basheer Arain; Abdul Rehman Nangraj (International Journal of Innovations in Science & Technology, 2025)
Data security is one of the most important aspects of the digital world as technology evolves and expands. Existing cryptographic systems are vulnerable due to quantum threats. The integration of Artificial Intelligence with Quantum Cryptography is an emerging field. AI-driven methods in QC to mitigate and be robust against the quantum threat. Quantum computing uses quantum mechanics to process data very quickly and accurately. Quantum Machine Learning can process big data as compare to classical methods with much more efficiency. The synergistic combination improves the threat detection and classification with accuracy. The integration also significantly enhances the speed and scalability of the large-scale deployment. AI enhances the efficiency and security of QC systems, and the challenges and opportunities of using AI-powered integration of quantum computing are reviewed.